What Social Scientists Have Learned About Civic Education: A Review of the Literature. Issue 1 (1st January 2019) - Campbell, David E.
Abstract: Historically there has been a relative dearth of social science research into civic education—even in political science, a discipline that had civic education as one of its founding objectives. This is partly due to the mistaken impression that civics instruction has no effect on civic and political participation, a conclusion that was once conventional wisdom but has since been refuted. More and more evidence has accumulated that well-designed civic education—both formal and informal—has meaningful, long-lasting effects on the civic engagement of young people. Existing research finds four aspects of schooling that affect civic learning and engagement: classroom instruction, extracurricular activities, service learning, and a school's ethos. Furthermore, state-level civics exams can positively affect knowledge about politics and government. The unifying theme that arises from this burgeoning literature is that effective civic education can compensate for a dearth of civic resources in the home and community. However, the renaissance of research into civic education is only just beginning, as more needs to be done. The existing data are too limited, and randomized studies are rare. Truly advancing our understanding of civic education will require a large-scale, multi-method, interdisciplinary effort.